Pengaruh Etos Kerja Terhadap Kinerja Organisasi Resimen pada Kampus Politeknik Penerbangan Medan - Sijabat, Jhon Fernando; Sirait, Donna N. M (UNIVERSITAS SERAMBI MEKKAH, 2024)
The success of an organization cannot be separated from increasing superior and quality human resources which must always be managed and emphasized by the organization in order to achieve the expected performance. This research uses a quantitative and qualitative approach, namely by observing learning from the work ethic itself. Work ethic is one of the mandatory lessons for students to become Medan Aviation Polytechnic graduates who will have a good work ethic in the future. The Influence of Work Ethic on Student Performance. The results of the research show that work ethic has a positive and significant influence on student performance in the Medan Aviation Polytechnic regiment organization. This means that work ethic is one of the variables that influences student performance. The work ethic factor has the greatest influence on student performance in this research.